Preferences of melanoma patients to accept adjuvant therapy and toxicity – a qualitative substudy of the GerMelaTox-A project - Toni Maria Janke; Laura Moysig; Christine Blome; Katharina C. Kähler (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Targeted treatment and immunotherapy, both adjuvant treatment options, come with a certain toxicity and can cause severe side effects. To date, data about the underlying reasons for patients to accept or reject specific types of adjuvant therapy is scarce. Therefore, this study investigates the motives of melanoma patients for tolerating or rejecting adjuvant therapy and its side effects. Methods We conducted semi-structured interviews with a subsample of patients to investigate the underlying reasons for treatment decisions in a quantitative treatment-trade off study. Categorisation was conducted using qualitative content analysis. Results The 17 participants had a mean age of 55.5 years and 12 were female. The final category system covered three clusters. The cluster “type of therapy and therapy process” described therapy-related aspects that affect acceptability of adjuvant treatments. Prospect of treatment benefit and side effects were important aspects. Route of administration and physician visits should be convenient. The cluster “way of living” described the influence that activities and circumstances of life organisation have on acceptability. Participants wished treatment to affect everyday life as little as possible. Maintaining sufficient quality of life was mentioned to be crucial. The cluster “emotions and feelings” described optimism and hope but also mental strain originating from possible treatment options. Conclusion Patients in our study indicate high willingness to undergo adjuvant therapy, even when facing toxicity. The evaluation of potential side effects and prospects of treatment benefit is highly individual. Therefore, it is important to consider personal patient preferences to make appropriate and shared decision-making.